1986
DOI: 10.1093/jac/18.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bactericidal action of mouse macrophages by subinhibitory concentrations of monobactams

Abstract: The effects of sub-minimum inhibitory concentrations (sub-MICs) of monobactams (aztreonam and AMA1080) on the host-parasite relationship were studied in an in vitro system using an established mouse macrophage cell line. The presence of sub-MICs aztreonam or AMA1080 enhanced significantly the macrophage bactericidal activity against Escherichia coli S615, Pseudomonas aeruginosa K1, Klebsiella pneumoniae 12 and Serratia marcescens US5. Even four times the MIC of monobactams had no direct effect on macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Treatment of bacterial infections is closely related not on ly to the direct antibacterial action of antibiot ics but also to the host defence mechanisms such as phagocytes (polymorphonuclear leu kocytes and macrophages) and complement. For these reasons, in vitro studies have been performed regarding the interaction between antibiotics at a sub-MIC and host defence mechanisms [20][21][22]. Wc previously studied the in vitro interaction among cefodizime, bacteria (Escherichia coli and Pseudomonas aeruginosa) and mouse polymorphonuclear leukocytes and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of bacterial infections is closely related not on ly to the direct antibacterial action of antibiot ics but also to the host defence mechanisms such as phagocytes (polymorphonuclear leu kocytes and macrophages) and complement. For these reasons, in vitro studies have been performed regarding the interaction between antibiotics at a sub-MIC and host defence mechanisms [20][21][22]. Wc previously studied the in vitro interaction among cefodizime, bacteria (Escherichia coli and Pseudomonas aeruginosa) and mouse polymorphonuclear leukocytes and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers found that the function of alveolar macrophages rather than a change in the number of these phagocytes in the lungs decreased with age [80]. Subinhibitory concentrations of antibiotics can also increase susceptibility to killing by host macrophages, a phenomenon linked to altered capsule thickness, surface hydrophobicity, and charge [89][90][91].…”
Section: Phagocytes and Host Defense Against K Pneumoniaementioning
confidence: 99%
“…Te classes of antibiotics used in this study and their mechanisms of action were obtained from previous studies.Class of antibioticsAntibioticsMechanism of actionReferences Penicillin Ampicillin, piperacillin, piperacillin-tazobactam, and cefepime Disrupt the synthesis of the peptidoglycan layer of bacterial cell walls[34] Penicillin combinations Amoxicillin/clavulanate Te second component reduces the efectiveness of some forms of bacterial resistance to the frst component the synthesis of the peptidoglycan layer of bacterial cell walls[36] Carbapenems Imipenem, meropenem…”
mentioning
confidence: 99%